Understanding Genesis - Sarna, Nahum M (New York : Schocken Books, 1970)
"Schocken paperbacks on Jewish life and religion ; SB 253." Includes bibliographical references (pages 235-245) and indexes. Table of Contents: Creation -- The flood -- The tower of Babel -- The patriarchal period -- From Mesopotamia to Canaan -- The battle of the kings -- Sodom and Gomorrah -- The birth of Isaac and the Akedah -- Winding up affairs -- Jacob and Esau -- Jacob and Laban -- Joseph
Creation -- The flood -- The tower of Babel -- The patriarchal period -- From Mesopotamia to Canaan -- The battle of the kings -- Sodom and Gomorrah -- The birth of Isaac and the Akedah -- Winding up affairs -- Jacob and Esau -- Jacob and Laban -- Joseph
"Schocken paperbacks on Jewish life and religion; SB 253."
Includes bibliographical references (pages 235-245) and indexes
Keywords: Bible. -- Commentaries; Book of Genesis - Introduction; Genesis- Extra Biblical Evidences